Failure Behavior and Damage Characteristics of Coal at Different Depths under Triaxial Unloading Based on Acoustic Emission - Anlin Zhang; Ru Zhang; Mingzhong Gao; Zetian Zhang; Zheqiang Jia; Zhaopeng Zhang; Ersheng Zha (Energies, 2020)
The depth effect of coal mechanical behavior seriously affects the safety and efficiency of deep coal mining. To explore the differences in failure behavior and damage characteristics of coal masses at different depths during the coal mining process, based on the consideration of in situ stress environment, physical properties, and mining disturbance of coal seams, triaxial unloading experiments with acoustic emission (AE) monitoring were conducted on coal samples at four different depths taken from the Pingdingshan coal mine area. The results showed that the AE activity of deep coal was more concentrated, and the cumulative AE energy of coal increased with increasing depth. The cumulative AE energy of the 1050-m coal sample was 69 times that of the 300-m coal sample. The b value representing the microcrack scale decreased with increasing depth, and the rupture degree of deep coal increased. The cracking mode of coal was classified and the failure behavior was analyzed. The cumulative tensile crack percentage of coal increased with increasing depth, and the tensile–shear composite failure occurred in the 300-m coal sample, whereas significant tensile failure occurred in the 1050-m coal sample. In addition, the damage evolution process of coal was divided into three stages, and the characteristic stress of coal was obtained. The ratio of crack initiation stress (σci) to peak stress (σc) increased with increasing depth, and the damage evolution process of deep coal was more rapid. The research results can provide useful guidance for disaster prevention and evaluation of surrounding rock stability during deep coal resource mining in the Pingdingshan coal mine area.